A BIM-based construction claim management model for early identification and visualization of claims. Issue 2 (5th June 2020) - Parchami Jalal, Majid; Yavari Roushan, Tayebe; Noorzai, Esmatullah; Alizadeh, Maryam
Abstract : Purpose: This study aims at introducing a claim management model based on building information modeling (BIM) for claims that can be visualized in BIM models. Design/methodology/approach: Based on the results of a questionnaire survey, 10 claims were identified as claims that can be visualized in BIM models (named hard claims in this study). Then, a BIM-based claim management model was developed and used in a case study. Findings: A BIM-based claim management model is represented. The claim management process through this model consists of four steps: (1) extracting project information, identifying conditions prone to claim and storing them into a relational database, (2) automatically connecting the database to building information model, (3) simulation of the claims in building information model and (4) final calculations and report. Practical implications: The proposed model can provide benefits to parties involved in a claim, such as early identification of potential claims, large space for data storage, facilitated claim management processes, information consistency and improved collaboration. Originality/value: There are a few studies on providing solutions to claim management based on BIM process. Hence, the original contribution of this paper is the attempt to set a link between BIM and claim management processes.